Distribution of knock-down resistance mutations in Anopheles gambiae molecular forms in west and west-central Africa - Santolamazza, Federica (2021)
Background. Knock-down resistance (kdr) to DDT and pyrethroids in the major Afrotropical vector species, Anopheles gambiae sensu stricto, is associated with two alternative point mutations at amino acid position 1014 of the voltage-gated sodium channel gene, resulting in either a leucine-phenylalanine (L1014F), or a leucine-serine (L1014S) substitution. In An. gambiae S-form populations, the former mutation appears to be widespread in west Africa and has been recently reported from Uganda, while the latter, originally recorded in Kenya, has been recently found in Gabon, Cameroon and Equatorial Guinea. In M-form populations surveyed to date, only the L1014F mutation has been found, although less widespread and at lower frequencies than in sympatric S-form populations. Methods. Anopheles gambiae M- and S-form specimens from 19 sites from 11 west and west-central African countries were identified to molecular form and genotyped at the kdr locus either by Hot Oligonucleotide Ligation Assay (HOLA) or allele-specific PCR (AS-PCR). Results. The kdr genotype was determined for about 1,000 An. gambiae specimens. The L1014F allele was found at frequencies ranging from 6% to 100% in all S-form samples (N = 628), with the exception of two samples from Angola, where it was absent, and coexisted with the L1014S allele in samples from Cameroon, Gabon and north-western Angola. The L1014F allele was present in M-form samples (N = 354) from Benin, Nigeria, and Cameroon, where both M- and S-forms were sympatric. Conclusion. The results represent the most comprehensive effort to analyse the overall distribution of the L1014F and L1014S mutations in An. gambiae molecular forms, and will serve as baseline data for resistance monitoring. The overall picture shows that the emergence and spread of kdr alleles in An. gambiae is a dynamic process and that there is marked intra- and inter-form heterogeneity in resistance allele frequencies. Further studies are needed to determine: i) the importance of selection pressure exerted by both agricultural and public health use of pyrethroid insecticides, ii) the phenotypic effects, particularly when the two mutations co-occur; and iii) the epidemiological importance of kdr for both pyrethroid- and DDT-based malaria control operations, particularly if/when the two insecticides are to be used in concert.